An introduction to mathematical modeling : a course in mechanics - Oden, J. Tinsle [ (John Tinsley)] , 1936- (Wiley series in computational mechanics, 2011)
"An important resource, this book provides a short-course in nonlinear continuum mechanics, contains a brief account of electromagnetic wave theory and Maxwell's equations as well as an introductory account of quantum mechanics, and presents a brief introduction to statistical mechanics of systems in thermodynamic equilibrium. Also included is information on continuum mechanics, electrodynamics, quantum mechanics, and statistical mechanics"--Provided by publisher.